2005
DOI: 10.1021/jf047908j
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Transport and Transformation Associated with MSMA Application on a Golf Course Green

Abstract: The impact of extensively used arsenic-containing herbicides on groundwater beneath golf courses has become a topic of interest. Although currently used organoarsenicals are less toxic, their application into the environment may produce the more toxic inorganic arsenicals. The objective of this work was to understand the behavior of arsenic species in percolate water from monosodium methanearsonate (MSMA) applied golf course greens, as well as to determine the influences of rootzone media for United State Golf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
93
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(97 citation statements)
references
References 21 publications
4
93
0
Order By: Relevance
“…However, over the past few decades, As contamination of golf course soils due 69 to the use of As-based pesticides has become a topic of interest (Cai et al 2002;Feng et al 2005; 70 Pichler et al 2008). In general, most studies of As based pesticide application to golf course soils 71 have observed As contamination of underlying groundwater (Cai et al 2002;Feng et al 2005). The 72 manufactured herbicide monosodium methyl arsenate (MSMA) for example, uses organic As species 73 as its active ingredient and has been observed to leave a residue in amended soils (Rahman et al 74 2012).…”
Section: Inorganic 47mentioning
confidence: 99%
See 4 more Smart Citations
“…However, over the past few decades, As contamination of golf course soils due 69 to the use of As-based pesticides has become a topic of interest (Cai et al 2002;Feng et al 2005; 70 Pichler et al 2008). In general, most studies of As based pesticide application to golf course soils 71 have observed As contamination of underlying groundwater (Cai et al 2002;Feng et al 2005). The 72 manufactured herbicide monosodium methyl arsenate (MSMA) for example, uses organic As species 73 as its active ingredient and has been observed to leave a residue in amended soils (Rahman et al 74 2012).…”
Section: Inorganic 47mentioning
confidence: 99%
“…The 72 manufactured herbicide monosodium methyl arsenate (MSMA) for example, uses organic As species 73 as its active ingredient and has been observed to leave a residue in amended soils (Rahman et al 74 2012). Although organic As is not toxic to humans, it can change speciation in soil environments to a 75 more toxic inorganic form following a series of chemical processes (Feng et al 2005; U.S. factor of 10 -3 to 10 -4 . This has also been supported by similar research data (Cohen et al, 2002).…”
Section: Inorganic 47mentioning
confidence: 99%
See 3 more Smart Citations